Os trabalhos não remunerados das mulheres rurais no Brasil: um estudo a partir dos dados da PNAD Contínua - 2018 - Viana, Raquel (2019)
This study aimed to analyze the particularities of the unpaid productive and reproductive work of women in rural Brazil. The totality of work that these women do free of charge, both in the sphere of production and reproduction / domestic. Theoretical assumptions are referenced in the Marxist tradition in dialogue with the elaborations in the field of materialist feminism and feminist economics. It reflected on the consubstantiality of social relations of sex, race and class, the sexual division of labor, domestic and care work as a basis for sustaining the subordination and exploitation of women in the capitalist-patriarchal-racist society. The empirical basis of our study was the microdata from the National Household Sample Survey - Continuous PNAD, conducted by the Brazilian Institute of Geography and Statistics - IBGE in 2018. We characterized the different forms of work performed by rural women with an emphasis on color or race variables. The result evidenced that men and women participate in reproductive / domestic work, but women remain the majority responsible for this type of work. Respectively, characteristics such as regularity and eventuality differentiate the reproductive / domestic work of women and men, respectively. The participation of men follows a hierarchy in the types and places where tasks are performed. Therefore, they perform more tasks in the public space and keep their distance from those considered ―female‖. Women's work does not recognize geographical boundaries and is executed either in public or private spaces and in the homes of relatives. Thus, the study showed that men, have a certain freedom, converted into a privilege that gives them the right to choose what type of activity they want to do. Thus, the study revealed that men, have a certain freedom, converted into a privilege that gives them the right to choose what type of activity they want to execute. In the work for own consumption, dynamics were a little different. In it, women make more progress in activities considered ―masculine‖, but in general, inequality remains, as the hours they dedicate to all unpaid jobs are higher than that of men. Most of those who perform unpaid work in rural areas are black (black and brown) with an evident sexual and racial division of labor. The condition of rural women in doubly unpaid jobs challenges us to deepen the reflection on the process of subordination and exploitation that they experience in their daily lives.